Effect of pectin and sucrose concentrations on the physical characteristics of seablite (Suaeda maritima) vegetable leather - Anggraeni, Sherly Nur; Dedin Finatsiyatul Rosida; Pratiwi, Yunita Satya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Suaeda maritima, a coastal plant, has potential as a functional food ingredient due to its high antioxidant content (80.36%) and the presence of vitamin A, beta-carotene, and vitamin E. The innovation of processing Suaeda maritima leaves into vegetable leather aims to enhance their utility and consumer acceptability. Vegetable leather is a plant-based product made by grinding and drying vegetables into flexible sheets. Adding pectin and sucrose is necessary to develop the texture and improve flavor. This study aimed to check the moisture content, pH, plastic texture (1st fracture deformation), and lightness of Suaeda maritima vegetable leather using different amounts of pectin (1%, 2%, 3%) and sucrose (15%, 20%, 25%). The experimental design used was a two-factor, completely randomized design (CRD) with two replications, followed by ANOVA and 5% DMRT analysis. The results showed that the best treatment was the combination of 3% pectin and 25% sucrose, which produced vegetable leather with a moisture content of 19.48%, pH of 3.67, 1st fracture deformation value of 0.03 mm, and a lightness value of 32.01. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero hungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 14: Life Below Water